The fraud diamond: element in detecting financial statement of fraud - Rengganis, RR. Maria Yulia Dwi; Sari, Maria Mediatrix Ratna; Budiasih, I.G.A.N; Wirajaya, I Gde Ary; Suprasto, Herkulanus Bambang (International research journal of management, IT and social sciences, 2019)
The financial statement fraud is generally difficult to be detected, because of the various motivations behind the actions taken. The purpose of this research is to analyze the elements of fraud diamond in detecting financial statement fraud by looking at the influence of variables into a proxy of the elements of fraud diamond on financial statement fraud. The population of this research is the entire financial sector companies registered in BEI 2013-2017 period. Purposive sampling technique was used to determine sample research. The company elected to sample as many as 46 companies. The research method used is the method of multiple linear regression analysis. The results of the analysis of this study are pressure elements showing only financial target variables have positive effect on financial statement fraud. The opportunity element shows variable number for audit committees, independent commissioners and the number of audit committee meetings have negative affect. The rationalization element shows that the audit opinion variable has no effect on financial statement fraud. The capability element shows that the change of director’s variable has no effect on financial statement fraud.